If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 2.8 = 4.56 Reorder the terms: 2.8 + y = 4.56 Solving 2.8 + y = 4.56 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2.8' to each side of the equation. 2.8 + -2.8 + y = 4.56 + -2.8 Combine like terms: 2.8 + -2.8 = 0.0 0.0 + y = 4.56 + -2.8 y = 4.56 + -2.8 Combine like terms: 4.56 + -2.8 = 1.76 y = 1.76 Simplifying y = 1.76
| 10x^2-3=13 | | (81x^2)^(1/4)*(9x^3)^(1/2) | | 13-1/6y | | 10x+15+3x+3=37 | | 6(t-3)+6t=4(3t+3)-1 | | 14x+15=40 | | 5/4*8=18 | | 14x+15=105(5x-65) | | 3(2h-6)(-2h+1)=9 | | 0.2(0.1x+0.1)=-0.6 | | 10x^2-17x+2= | | -2x-1=30 | | 4(2p+1)-12=2(8p+12) | | x^2+6x+8=2 | | 64-x^3= | | -4n+4-4n= | | x(64-x^3)= | | 8-x+3x-3-9x= | | 4/11x=24 | | 1710a^3-600a^2-600a-600=0 | | -5b-6/7-5+3b/7 | | 6x^2-5x+5= | | 1/2(2x-7)=7 | | V=6nzt+6nz^2 | | 19a^2-10a-10=0 | | 8(3)+3y=48 | | 8x+3(0)=48 | | 8(0)+3y=48 | | (x+8)(y-4)=90 | | (x+8)*(y-4)=90 | | 2(4x+1)-3(2x-3)=5 | | 10x^2-y^2=100 |